Genomic Regions From an Iranian Landrace Increase Kernel Size in Durum Wheat - Desiderio, Francesca; Zarei, Leila; Licciardello, Stefania; Cheghamirza, Kianoosh; Farshadfar, Ezatollah; Virzi, Nino; Sciacca, Fabiola; Bagnaresi, Paolo; Battaglia, Raffaella; Guerra, Davide; Palumbo, Massimo; Cattivelli, Luigi; et al. (Frontiers in Plant Science, 2019)
Kernel size and shape are important parameters determining the wheat profitability, being main determinants of yield and its technological quality. In this study, a segregating population of 118 recombinant inbred lines derived from a cross between the Iranian durum landrace accession ‘Iran_249’ and the Iranian durum cultivar ‘Zardak’ was used to investigate durum wheat kernel morphology factors and their relationships with kernel weight, and to map the corresponding QTLs. A high density genetic map, based on wheat 90k iSelect Infinium SNP assay, comprising 6195 markers, was developed and used to perform the QTL analysis for kernel length and width, traits related to kernel shape and weight, and heading date, using phenotypic data from three environments. Overall, a total of 31 different QTLs and 9 QTL interactions for kernel size, and 21 different QTLs and 5 QTL interactions for kernel shape were identified. The landrace Iran_249 contributed the allele with positive effect for most of the QTLs related to kernel length and kernel weight suggesting that the landrace might have considerable potential toward enhancing the existing gene pool for grain shape and size traits and for further yield improvement in wheat. The correlation among traits and co-localization of corresponding QTLs permitted to define 11 clusters suggesting causal relationships between simplest kernel size trait, like kernel length and width, and more complex secondary trait, like kernel shape and weight related traits. Lastly, the recent release of the T. durum reference genome sequence allowed to define the physical interval of our QTL/clusters and to hypothesize novel candidate genes inspecting the gene content of the genomic regions associated to target traits.